2011
DOI: 10.1038/npp.2011.256
|View full text |Cite
|
Sign up to set email alerts
|

Consolidation of Remote Fear Memories Involves Corticotropin-Releasing Hormone (CRH) Receptor Type 1-Mediated Enhancement of AMPA Receptor GluR1 Signaling in the Dentate Gyrus

Abstract: Persistent dreadful memories and hyperarousal constitute prominent psychopathological features of posttraumatic stress disorder (PTSD). Here, we used a contextual fear conditioning paradigm to demonstrate that conditional genetic deletion of corticotropin-releasing hormone (CRH) receptor 1 within the limbic forebrain in mice significantly reduced remote, but not recent, associative and non-associative fear memories. Per os treatment with the selective CRHR1 antagonist DMP696 (3 mg/kg) attenuated consolidation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 52 publications
1
32
0
Order By: Relevance
“…Since indeed none of the protocols in our model showed significant long-term changes in CRFR1, we suggest that the initiation of the stress response has indeed subsided. In fact, Thoeringer et al (2012) show that traumatic memories in the hippocampus can be reversed by CRFR1 antagonists only within the first week after the trauma. So if CRFR1 activity does not regulate long-term responses to PTSD and PTSD is a pathology that can last for years, then the shutting off of the response to the trauma must be impaired.…”
Section: Discussionmentioning
confidence: 94%
“…Since indeed none of the protocols in our model showed significant long-term changes in CRFR1, we suggest that the initiation of the stress response has indeed subsided. In fact, Thoeringer et al (2012) show that traumatic memories in the hippocampus can be reversed by CRFR1 antagonists only within the first week after the trauma. So if CRFR1 activity does not regulate long-term responses to PTSD and PTSD is a pathology that can last for years, then the shutting off of the response to the trauma must be impaired.…”
Section: Discussionmentioning
confidence: 94%
“…Crh over-expression was followed by a decreased CRHR1 receptor density within the BNST suggesting that "behavioral effects may be mediated by enhanced CRH receptor signaling or compensatory changes in CRF receptor density within these structures" 66 . Importantly, CRH over-expression was impairing anxiety responses towards threat cues if administered prior to conditioning, and also, limbic CRHR1 was shown to be required for the enhancement of fear memory consolidation 8 . Together these data suggest an important role for CRHR1 in the formation and generalization of fear.…”
Section: Discussionmentioning
confidence: 99%
“…These data suggest an important role of CRHR1 in short-and long-term adaptive responses to stress, probably by attenuating the impact of circulating ACTH and CORT, while CRHR1 directly exerts negative effects on learning and hippocampal morphology as a response to stress. Further adding to this, it was shown that limbic CRHR1 enhances the consolidation of fear memories 8 .…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…CORT has also been shown to interact with catecholamines in the basolateral amygdala to intensify long-term memory consolidation of emotional events . However, CRF1 receptor-deficient mice (deficient in CORT elevation) showed normal fear learning (Tovote et al 2005) and displayed decreased remote, but not recent, contextual fear memory (Thoeringer et al 2012).…”
Section: Glucocorticoid Hypothesis Of Stress: Compatible and Incompatmentioning
confidence: 99%